Diferrate [Fe2(CO)6(μ‐CO){μ‐P(aryl)2}]− as Self‐Assembling Iron/Phosphor‐Based Catalyst for the Hydrogen Evolution Reaction in Photocatalytic Proton Reduction—Spectroscopic Insights. Issue 60 (19th October 2018) - Fischer, Steffen; Rösel, Arend; Kammer, Anja; Barsch, Enrico; Schoch, Roland; Junge, Henrik; Bauer, Matthias; Beller, Matthias; Ludwig, Ralf
Abstract: This work is focused on the identification and investigation of the catalytically relevant key iron species in a photocatalytic proton reduction system described by Beller and co‐workers. The system is driven by visible light and consists of the low‐cost [Fe3 (CO)12 ] as catalyst precursor, electron‐poor phosphines P(R)3 as co‐catalysts, and a standard iridium‐based photosensitizer dissolved in a mixture of THF, water, and the sacrificial reagent triethylamine. The catalytic reaction system was investigated by operando continuous‐flow FTIR spectroscopy coupled with H2 gas volumetry, as well as by X‐ray absorption spectroscopy, NMR spectroscopy, DFT calculations, and cyclic voltammetry. Several iron carbonyl species were identified, all of which emerge throughout the catalytic process. Depending on the applied P(R)3, the iron carbonyl species were finally converted into [Fe2 (CO)6 (μ‐CO){μ‐P(R)2 }] − . This involves a P−C cleavage reaction. The requirements of P(R)3 and the necessary reaction conditions are specified. [Fe2 (CO)6 (μ‐CO){μ‐P(R)2 }] − represents a self‐assembling, sulfur‐free [FeFe]‐hydrogenase active‐site mimic and shows good catalytic activity if the substituent R is electron poor. Deactivation mechanisms have also been investigated, for example, the decomposition of the photosensitizer or processes observed in the case of excessive amounts of P(R)3 . [Fe2 (CO)6 (μ‐CO){μ‐P(R)2 }] − has potential for future applications. Abstract : Hydrogen gas evolution : The diferrate complex represents the key species in a photocatalytic proton reduction system that is driven by visible light and consists of low‐cost catalyst precursors, electron‐poor phosphines, and a standard iridium‐based photosensitizer (see scheme). The self‐assembling, sulfur‐free [FeFe]‐hydrogenase mimic shows good catalytic activity, which has been characterized by operando continuous‐flow FTIR spectroscopy coupled with hydrogen gas volumetry, XAS, and NMR spectroscopy.